Clinical features in adult multiple sclerosis patients - Koprivnik, Matej (Obzornik zdravstvene nege, 2020)
Introduction: The purpose of the study was to identify possible correlations between the quality of life, neurological disability, and functional ability in patients with multiple sclerosis. Methods: 258 patients with multiple sclerosis were included in the cross-sectional study. They were assessed with the Expanded Disability Status Scale (EDSS), the Berg Balance Scale (BBS), the Timed 25-Foot Walk Test (T25-FW), the 9-Hole Peg Test (9HPT), the Paced Auditory Serial Addition Test (PASAT-3) and the EQ visual analogue scale (EQ-VAS). Inferential statistics were used. Results: A positive correlation between the EQ-VAS and the BBS (r = 0.43, p < 0.01 ) and the PASAT-3 (r =%0.19, p < 0.01), and a negative correlation between the EQ-VAS and the T25FW (r = %0.42, p < 0.01) and the 9-HPT (r = %0.40, p < 0.01) were shown. A negative correlation was also observed between the EDSS and the BBS (r = %0.77, p < 0.05) as well as the EDSS and the PASAT-3 (r = %0.25, p < 0.01), and a positive correlation between the EDSS and the 9 HPT (r = 0.67, p < 0.01) and the T25-FW (r = 0.80, p < 0.01). Discussion and conclusion: Associations between the variables indicate the need for complex, personalized and rational monitoring of patients with multiple sclerosis.
Keywords: functional ability; funkcionalne sposobnosti; kakovost življenja; multipla skleroza; multiple sclerosis; neurological disability; nevrološka prizadetost; quality of life